The Effect of Social Support on Stress Coping in People with HIV - Irfan, Muh; Nurdin, Muh Nur Hidayat; Ansar, Wilda (Polteknik Ilmu Pemasyarakatan, 2023)
The high stress experienced by ODHIV requires adaptive coping. Negative stigma in society exacerbates the situation so that ODHIV do not get social support which is very important in dealing with stress or problems. This study aims to determine the impact of social support on stress coping among ODHIV in Makassar. This study involved 56 respondents respondents aged around 15-50 years taken from the Gaya Celebes Foundation (YGC), social support group care foundations (YPKDS), and hospitals. The research method employs a quantitative survey approach. The measuring instruments used in this study were The Brief Cope (Carver, 1997) and the Multidimensional Social Support (MSPSS) (Zimet, Dahlem, Zimet, & Farley 1988 The results showed that the value of the Wald test sig. value of 0.001 (p < 0.05) means that the null hypothesis (H0) is rejected and the alternative hypothesis is accepted. Thus, it can be concluded that there is a significant influence of social support on stress coping in people with HIV with a Negelkerke R Square value of 42,3% where the greater the social support received by ODHIV, the greater the possibility of coping with stress adaptively.